2019
DOI: 10.21203/rs.2.12883/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A small dose of remifentanil pretreatment suppresses sufentanil-induced cough during general anesthesia induction: a randomized, double-blind, placebo-controlled trial

Abstract: Background: Intravenous use of sufentanil can elicit cough. This study aimed to evaluate the inhibitory effect of pre-injection of a mall dose of remifentanil on sufentanil-induced cough during the induction of general anesthesia. Methods: This prospective, randomized, controlled trial was conducted from January 10, 2019 to March 01, 2019. A total of 100 patients undergoing elective surgery under general anesthesia were enrolled, and at last 84 patients were included and randomly allocated into two equal size … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The frequency of cough within 1 min following sufentanil injection was recorded, and the severity was graded depending on the cough frequency (mild, 1-2; moderate, 3-4; severe, ≥ 5, [12,13]).…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of cough within 1 min following sufentanil injection was recorded, and the severity was graded depending on the cough frequency (mild, 1-2; moderate, 3-4; severe, ≥ 5, [12,13]).…”
Section: Methodsmentioning
confidence: 99%
“…Explosive coughs may increase intra-abdominal pressure, increasing the risk of regurgitation and aspiration [5]. Clinical interventions, such as pretreatment with drugs (butorphanol, dezocine, remifentanil, and dexmedetomidine), changing the administration route or diluting the concentration of sufentanil, have been reported to reduce SIC [1][2][3][6][7][8][9][10][11][12][13]. However, the interventions could not be widely implemented in clinical practice due to several side effects such as long onset time, bradycardia, and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…It can inhibit μ and κ agonists and exert obvious antitussive effects by directly acting on the cough center of the medulla oblongata [14]. A previous study found that preemptive use of a small dose of opioids could suppress opioid-induced cough without applying additional drugs [10,15,16]. In this study, we explored the effect of pretreating patients with a small dose of oxycodone and sufentanil on the incidence and severity of SIC when larger doses of sufentanil (0.4 μg/kg) were subsequently administered during the induction of general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that pre-injection of low-dose fentanyl (0.5 μg⋅kg −1 or 25 μg directly) can alleviate FIC to some extent ( Du et al, 2014 ; Golmohammadi et al, 2018 ; Hung et al, 2010 ; Shrestha et al, 2012 ). Pretreatment with a small dose of remifentanil 0.3 μg⋅kg −1 , 1 min before sufentanil injection can effectively and safely reduce the incidence of cough induced by sufentanil (4.8% vs. 31%) ( Lin et al, 2019 ).…”
Section: Prevention and Treatment Of Fentanyl-induced Coughmentioning
confidence: 99%